2016
DOI: 10.1177/1043659616628964
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a Cancer Literacy Measure for Use Among Navajo Women

Abstract: Purpose The authors designed a community-based participatory research study to develop and test a family-based behavioral intervention to improve cancer literacy and promote mammography among Navajo women. Methods Using data from focus groups and discussions with a community advisory committee, they adapted an existing questionnaire to assess cancer knowledge, barriers to mammography, and cancer beliefs for use among Navajo women. Questions measuring health literacy, numeracy, self-efficacy, cancer communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…In contrast to our findings, other researchers have found evidence suggesting that traditionality may hinder participation in cancer screening (Canales et al, 2007;Solomon & Gottlieb, 1999;Yost et al, 2017). For example, Canales et al (2007), in their study with 115 Indigenous women in Vermont, reported an inverse relationship between traditionality (e.g., traditional Indian healer use) and mammogram screening.…”
Section: Enabling Factorscontrasting
confidence: 99%
“…In contrast to our findings, other researchers have found evidence suggesting that traditionality may hinder participation in cancer screening (Canales et al, 2007;Solomon & Gottlieb, 1999;Yost et al, 2017). For example, Canales et al (2007), in their study with 115 Indigenous women in Vermont, reported an inverse relationship between traditionality (e.g., traditional Indian healer use) and mammogram screening.…”
Section: Enabling Factorscontrasting
confidence: 99%
“…The resulting measure contains 129 items, including items measuring demographic variables, cancer history, screening behaviors, interactions with the health care system, experiences with interpreters, and beliefs, attitudes, emotions, and knowledge related to breast and cervical cancer. The measure has since been adapted for use with African American, Navajo, and Uruguayan women (Buki & Reich, 2011; Mayfield, 2012; Yost et al, 2016). A copy of the measure is available by request from Dr. Buki.…”
Section: Resultsmentioning
confidence: 99%
“…Home-based interviews were conducted in (written or oral) English, Navajo, or both. 9 Measures were adapted from English to Navajo with translations reviewed by the CAC and tested in focus groups. 9 Assessments included sociodemographics, a measure of BC literacy adapted by the research team 9 and open-ended questions about intervention helpfulness, and likes/dislikes.…”
Section: Methodsmentioning
confidence: 99%
“…The Navajo BC literacy measure, 15 administered at baseline for both participants and support persons, and among participants again at 3-months, measured: (1) mammography barriers, (2) cancer beliefs, (3) cancer knowledge, (4) health literacy, (5) numeracy, (6) self-efficacy, (7) cancer communication, (8) and family support for screening. 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation